Navigating Carbon Trading Implementation in the Indonesian Stock Exchange IDXCarbon: Challenges and Opportunities - Olii, Rahmat (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Global capital markets are increasingly aware of the urgency of addressing climate change by implementing various policies to reduce carbon emissions. One increasingly popular approach is carbon pricing, which aims to encourage companies to reduce emissions by factoring environmental costs into their investment decisions. In Indonesia, the capital market is under pressure to follow similar steps, especially in light of the Paris Agreement and the Indonesian government's commitment to reducing carbon emissions. This research investigates the challenges and opportunities in implementing carbon pricing in the Indonesian capital market IDX Carbon. Through in-depth literature analysis, this research identifies the factors that influence the implementation process and its impact on capital market stakeholders, including investors, companies and regulators. One of the main challenges is the complexity of the Indonesian capital market structure, such as low liquidity, the dominance of certain sectors in the index, and a lack of environmental awareness among investors. However, there are huge opportunities to introduce carbon pricing, such as increasing transparency and reporting of carbon emissions, providing economic incentives for green performing companies, and increasing environmental awareness among investors. It is hoped that the results of this research will provide valuable insights for regulators and capital market players in designing effective policies to reduce carbon emissions and increase economic sustainability.